Local perspective on a rare brain tumour: adult medulloblastoma. Issue 5 (14th May 2013) - Wong, S. F.; Mak, G.; Rosenthal, M. A.; Cher, L.; Gan, H. K.
Abstract Background Little contemporary data are available regarding Australian patterns of care in adult medulloblastoma. It is unclear whether treatment, extrapolated from paediatric protocols despite known differences between the two groups, results in comparable efficacy. Aim To perform a retrospective review of patterns of care in adult medulloblastoma, especially with respect to adjuvant chemotherapy, in Australian patients. Methods All medulloblastoma patients aged 15 years or older at two neuro‐oncology institutions were identified from January 1995–May 2011. Patients with supratentorial or peripheral tumours were excluded. Standardised data were extracted from each institution regarding symptoms, disease staging, treatments received, toxicities and survival outcomes. Results Seventeen eligible patients were identified. Median age was 37 years (range 20–67 years). All had good performance status (Eastern Cooperative Oncology Group 0–1). There were 11 standard‐risk de novo patients, three high‐risk de novo patients and three patients with recurrent disease. Median overall survival (OS) had not been reached for standard‐risk patients with median follow up of 58 months. The median OS for high‐risk de novo patients was 21 months, while the median OS was 15 months for patients with recurrent disease. Treatment was well tolerated, with haematological toxicities being most common. Conclusions Combined modality therapy (surgery followed by postoperative radiotherapy and adjuvant chemotherapy) was well tolerated and associated with good outcomes in standard‐risk de novo patients. High‐risk and recurrent disease patients do extremely poorly regardless of treatment and better treatment strategies are needed in these patients.